EGPI-1, a novel eIF4E/eIF4G interaction inhibitor, inhibits lung cancer cell growth and angiogenesis through Ras/MNK/ERK/eIF4E signaling pathway. (25th January 2022) - Qi, Xueju; Zhang, Shuna; Chen, Zekun; Wang, Lijun; Zhu, Wenyong; Yin, Chuanjin; Fan, Junting; Wu, Xiaochen; Wang, Jing; Guo, Chuanlong
Abstract: eIF4E plays an important role in regulating tumor growth and angiogenesis, and eIF4E is highly expressed in a variety of lung cancer cell lines. siRNA eIF4E can significantly inhibit the proliferation of lung cancer cells, indicating that inhibition of eIF4E may become a novel anti-tumor target. In the previous study, we synthesized a series of small molecule compounds with the potential to inhibit eIF4E. Among them, the compound EGPI-1 significantly inhibited the proliferation of a variety of lung cancer cells such as A549, NCI-H460, NCI-H1650 and 95D without inhibiting the proliferation of HUVEC cells. Further studies found that EGPI-1 interfered with the eIF4E/eIF4G interaction and inhibited the phosphorylation of eIF4E in NCI-H460 cells. The results of flow cytometry showed that EGPI-1 induced apoptosis and G0/G1 cycle arrest in NCI-H460 cell. Interestingly, we also found that EGPI-1 induced autophagy and DNA damage in NCI-H460 cells. The mechanism results showed that EGPI-1 inhibited the Ras/MNK/ERK/eIF4E signaling pathway. Moreover, EGPI-1 inhibited tube formation of HUVECs, as well as inhibited the neovascularization of CAM, proving the anti-angiogenesis activity of EGPI-1. The NCI-H460 xenograft studies showed that EGPI-1 inhibited tumor growth and angiogenesis in vivo by regulating Ras/MNK/ERK/eIF4E pathway. Our studies proved that eIF4E was a novel target for regulating tumor growth, and the eIF4E/eIF4G interaction inhibitor EGPI-1 was promising to develop into a novel anti-lung cancer drug. Graphical abstract: Image 1 Highlights: eIF4E plays an important role in regulating tumor growth and angiogenesis. Novel small molecule EGPI-1 inhibits eIF4E/eIF4G interaction. EGPI-1 exhibits anti-tumor and anti-angiogenesis activities in vivo and in vitro . EGPI-1 exerts anti-tumor and anti-angiogenesis effects by regulating the Ras/MNK/ERK/eIF4E signaling pathway.